Temperament of Indigenous Cattle and Buffaloes and its Effect on their Performance, Health and Welfare (Indian Journal of Animal Production and Management, 2024)
Temperament of dairy animal is the individual  behavioural difference in response to the  surrounding condition. In dairy bovines, the  temperament is most important at milking because  it affects efficiency of milking, milk yield and quality.  Temperament negatively affects the production,  reproduction, health and welfare. The temperament  of dairy bovines has moderate heritability with wide  variation from 0.07 to 0.53, indicates greater  influence of environmental factors on this trait.  Temperament shows low to moderate consistency  within the individual dairy animal (repeatability = 0.04-0.56). Prepartum management interventions  of dairy cattle and buffaloes particularly in  primiparous animals enable them to be calmer  during post-calving period which subsequently  improves their production and reproduction  performance, health and welfare. Therefore,  management interventions particularly before  calving can improve the temperament of indigenous  dairy cattle and buffaloes as well as their  performance.
Keywords: temperament; production; reproduction; health; welfare